КРУТНИЙ МОМЕНТ ТА НАГРІВАННЯ МАГНІТІВ У ДВИГУНІ З ПОВЕРХНЕВИМ РОЗТАШУВАННЯМ ПОСТІЙНИХ МАГНІТІВ: ПОРІВНЯННЯ ЗУБЧАСТОГО ТА БЕЗПАЗОВОГО СТАТОРА - Петухов, І.С.; Ісаєв, Є.В. (Інститут електродинаміки НАН України, Київ, 2026)
The advantages and disadvantages of two permanent magnet motor designs – slotted and slotless – are analyzed. A commercially available micromotor was adopted as the slotted design. Their performance is compared in terms of torque production and permanent magnet heating under intensive operating conditions. The rotor geometry was assumed to be identical, the maximum flux density in the magnetic cores was set to 1,7 T, and the rotational speed was considered constant. Modeling was carried out using COMSOL Multiphysics, with the results for the slotted design validated using the Simcenter Motorsolve software package. The torque and the amplitude of torque pulsations for both designs were evaluated, and the differences between them were analyzed. The causes of magnetic flux density pulsations in the magnets were studied, and their impact on eddy current losses was assessed. Numerical results for the output parameter ratios of the two designs were presented. The possibility of neglecting magnet heating in the slotless design was emphasized. References 11, figures 8, table 1.